Effectiveness of Virtual Technology Based Training for Posyandu Cadres in Preventing Stunting - Nurul Muchlisa; Aynun Abdi Putri Bausad; Saripa Saripa (Universitas Malahayati, 2026)
ABSTRACT Stunting is a major public health issue in Indonesia, with a national prevalence of 19.8% in 2024, including in Jeneponto Regency, which reaches 25-30% among toddlers. The role of Posyandu cadres is crucial in prevention, but it is limited by low knowledge of stunting prevention, anthropometric measurements, and nutrition education. Virtual technology-based training, such as via Zoom, is expected to efficiently enhance cadre capacity. The purpose of this study is to assess the effectiveness of virtual training through Zoom in improving the knowledge of Posyandu cadres regarding stunting prevention in Benteng and Pallengu Villages, Bangkala Subdistrict, Jeneponto Regency. The research method used is a quasi-experimental study with a pre-post test with control group design. The sample consisted of 52 cadres (26 intervention, 26 control) selected by simple random sampling. The intervention involved virtual training on stunting prevention, anthropometry, and nutrition education. Data were analyzed using the Wilcoxon test in SPSS. The results showed that in the intervention group, knowledge significantly increased from a pre-test mean of 61.52 ± 18.37 to a post-test mean of 79.71 ± 13.17 (p=0.001). The control group only increased from 61.07 ± 16.22 to 69.89 ± 18.27 (p=0.332). The majority of respondents were aged 15-35 years (65.38%) and had secondary school education (80.77%). The conclusion is that virtual training is effective in improving cadre knowledge, supporting sustainable stunting prevention. Keywords: Stunting, Posyandu Cadres, Virtual Training, Zoom, Prevention.